A persistent-mode 0.5 T solid-nitrogen-cooled MgB2 magnet for MRI. (29th December 2016) - Ling, Jiayin; Voccio, John P; Hahn, Seungyong; Qu, Timing; Bascuñán, Juan; Iwasa, Yukikazu
Abstract: This paper presents construction details and test results of a persistent-mode 0.5 T MgB2 magnet developed at the Francis Bitter Magnet Laboratory, MIT. The magnet, of 276 mm inner diameter and 290 mm outer diameter, consisted of a stack of eight solenoidal coils with a total height of 460 mm. Each coil was wound with monofilament MgB2 wire, equipped with a persistent-current switch and terminated with a superconducting joint, forming an individual superconducting loop. Resistive solder joints connected the eight coils in series. The magnet, after being integrated into a testing system, immersed in solid nitrogen, was operated in a temperature range of 10–13 K. A two-stage cryocooler was deployed to cool a radiation shield and the cold mass that included mainly ∼60 kg of solid nitrogen and the magnet. The solid nitrogen was capable of providing a uniform and stable cryogenic environment to the magnet. The magnet sustained a 0.47 T magnetic field at its center persistently in a range of 10–13 K. The current in each coil was inversely calculated from the measured field profile to determine the performance of each coil in persistent-mode operation. Persistent-current switches were successfully operated in solid nitrogen for ramping the magnet. They were also designed to absorb magnetic energy in a protection mechanism; its effectiveness was evaluated in an induced quench.